PENERAPAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR KOGNITIF IPAS SISWA - Yulfa, Maria; Suryani Sahabuddin, Erma; Yusuf, Faidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by students' low cognitive learning outcomes in IPAS (Natural and Social Sciences), a result of instruction that remained teacher-dominated and failed to optimize student engagement. The study aimed to improve students' cognitive learning outcomes in IPAS through the implementation of the Team Games Tournament (TGT) cooperative learning model supported by flashcards. This Classroom Action Research (CAR) was conducted over two cycles with 34 fourth-grade students at UPT SPF SDN Kompleks IKIP 1, Makassar City. Data were collected through observation, learning outcome tests, and documentation. The results showed an improvement in student learning outcomes: performance was in the "sufficient" category during Cycle I and rose to the "good" category during Cycle II. Additionally, student engagement in the learning process increased. Thus, the implementation of the TGT cooperative learning model supported by flashcards proved effective in enhancing the cognitive learning outcomes of fourth-grade students in IPAS. Keywords: Cooperative Model, Team Games Tournament (TGT), flashcards, cognitive learning outcomes, IPAS.